Impacted "Button Battery" in The Nose - a Time Management Comparison - Rizki Saputra; Dolly Irfandy; Bestari Jaka Budiman (Majalah Kedokteran Andalas, 2023)
Introduction: Foreign body in the nose can increase morbidity if not managed properly and correctly. Button battery containing alkaline substances can cause liquefactive necrosis. Management removes the button battery immediately. Case report: Two cases of a 4-year-old boy and a 5-year-old girl with a foreign body button battery were reported in the right and left nasal cavity, removed the button battery and debridement under general anesthesia. Conclusion: Button battery in the nasal cavity can cause various complications in the form of nasal perforation, this depends on the length of mucosal contact with the battery, the age of the battery and it must be removed immediately. Prevention plays an important role in preventing foreign bodies in the nose.